PRODUCT STRUCTURE DIGITAL MODEL - Sineglazov, V.M.; Kyevorkov, S.G. (Proceedings of National Aviation University (archive), 2012)
Research results of representation of product structure made by means of CADDS5 computer-aided design (CAD) system, Product Data Management Optegra (PDM) system and Product Life Cycle Management Wind-chill system (PLM), are examined in this work. Analysis of structure component development and its storage in various systems is carried out. Algorithms of structure transformation required for correct representation of the structure are considered. Management analysis of electronic mockup presentation of the product structure is carried out for Windchill system.